Motivasi Belajar dan Self Regulated Learning pada Mahasiswa dengan Sistem Pembelajaran Jarak Jauh - Tsusayya, Tasya Dhiya; Umaroh, Siti Khumaidatul; Imawati, Diana (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2021)
This study aims to measure the effect of learning motivation on self regulated learning in the students of School Teacher Education who study remotely at the UPBJJ Samarinda Open University. This study used the Assessing Academic Self Regulated Learning Measurement Scale and the Learning Motivation Measurement Scale. This study involved 56 male students respondents and 236 female students respondent. Determination of the sample using proportional random sampling technique. The research data were analyzed using simple regression analysis techniques. The result revealed that the effect of learning motivation on self regulated learning shows that there is a positive effect of learning motivation on the self-regulated learning in students of School Teacher Education by a value of ð‘…2 41,1% with a significance value of 0,000 (P <0,05). This study recommends the importance of increasing learning motivation in students of School Teacher Education which can increase self regulated learning particularly in distance learning program.